Tri Wulan Muslimat Nahdlatul Ulama Recitation's Cultural Values in East Oku Regency - Siti Nashihah; Abdullah Idi; Mohammad Syawaludin; Imam Rodin (UIN Sumatera Utara Medan, 2023)
This article The NU Muslimat Quarterly Recitation in East OKU Regency is a routine activity that is carried out every three months by NU Muslimat administrators from the branch level to the sub-branch level in the region. This activity was held with the aim of strengthening ties of friendship between NU Muslimat administrators, branch children, and village communities with various tribes in East OKU. First held in 2004, this quarterly recitation was held after going through several stages of deliberation to determine the place, time of activity, speakers, implementing committee, and funding. Apart from being an event to strengthen friendship ties, this quarterly recitation activity can also become a science major that is beneficial to students and pilgrims. In this study, participants can add religious knowledge, be more obedient to Allah, and gain religious insight. Quarterly recitation is also able to create positive socio-cultural values. The use of Muslim batik uniforms by all NU Muslim members in this activity can create a sense of oneness among them. Even the local community seemed enthusiastic about this activity, with the appearance of impromptu sellers who sold various goods to the recitation congregation. This activity is beneficial not only for NU Muslimat administrators and congregations but also for the general public who take part in it.